Towards understanding the effects of magnesium addition on microstructural and thermal properties of NiAlCr alloys in as-cast and heat treated states - Azakli, Yunus; Tarakçı, Mehmet (Elsevier Science Sa, 2017)
The effects of magnesium addition on the microstructure, hardness, chemical composition and thermal expansion coefficient of NiAlCr alloys in as-cast and heat-treated states were studied. NiAlCr alloys containing 1, 2.5 and 3.8 at.% Mg were prepared via atmosphere-controlled induction melting following vacuum arc melting. According to the XRD results, as-cast alloys were mainly composed of martensite, beta-NiAl and gamma'-Ni3Al. High amounts of Mg in alloys resulted in a slight increase in CTE. Increasing Mg also changed the morphology of the interdendritic Ni3Al phase from continuous network to discontinuous structure, resulting in Ni2Mg precipitates with hardness of 1280 HV0.002. In the furnace cooling procedure following the annealing procedure at 1050 degrees C for 96 h, martensite completely transformed into beta-NiAl with alpha-Cr precipitates. The single phase Ni3Al transformed into Al0.9Ni4.22-Ni3Al lamellar structure and Ni2Mg phase disappeared. The presence of Mg in solid solution did not influence CTE of the alloys. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: NiAlCr; Ni2Mg; Microstructure; Thermal expansion; Hardness